1991
DOI: 10.1177/088840649101400105
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded View on Consultation Competencies for Educators Serving Culturally and Linguistically Diverse Exceptional Students

Abstract: The purpose of this article is to define educational consultation, review competencies needed by educational consultants, and specify those competencies essential for educators who serve children with special needs who are from culturally and linguistically diverse backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Research has indicated that ESL children can benefit when professionals collaborate to provide services for them (Murphy, DeEsch, & Strein, 1998;Ortiz & Wilkinson, 1991), but many practitioners feel unprepared to deal with this issue (Baca, 2000;West & Cannon, 1988;Harris & Evans, 1995;Harris, 1999). District leaders, principals, and teacher educators must have current knowledge about trends in effective professional development and the education of English language learners.…”
Section: Resultsmentioning
confidence: 97%
“…Research has indicated that ESL children can benefit when professionals collaborate to provide services for them (Murphy, DeEsch, & Strein, 1998;Ortiz & Wilkinson, 1991), but many practitioners feel unprepared to deal with this issue (Baca, 2000;West & Cannon, 1988;Harris & Evans, 1995;Harris, 1999). District leaders, principals, and teacher educators must have current knowledge about trends in effective professional development and the education of English language learners.…”
Section: Resultsmentioning
confidence: 97%
“…The purpose of this article is to delineate the competencies needed by education personnel in order to collaborate in a diverse teaching environment, to discuss the role of special education teachers, and to advocate for collaboration across disciplines. CULTURAL DIVERSITY AND COMPETENCIES FOR COLLABORATION Harris (1991) delineated consultation competencies for educators serving diverse exceptional students and discussed the implications of cultural diversity for the collaboration process. These competencies include, but are not limited to (a) understanding their personal perspectives about those who are culturally diverse, (b) using effective communication and problem-solving skills, (c) understanding their roles in the collaboration process, and (d) using appropriate evaluative and instructional methods.…”
Section: Jairrelsmentioning
confidence: 99%
“…Do they value them as human beings and believe that they are worthy recipients of a quality education? Harris (1991) asserted that collaborators must try to determine how these beliefs were formed. An honest assessment of one's knowledge base, beliefs, and value system may facilitate the collaborative process.…”
Section: Jairrelsmentioning
confidence: 99%
See 2 more Smart Citations